Yield and chemical composition of the essential oil of Moroccan chamomile [Cladanthus mixtus (L.) Chevall.] growing wild at different sites in Morocco†. (3rd March 2013) - Elouaddari, Anass; El Amrani, Abdelaziz; Eddine, Jamal Jamal; Correia, A. Isabel D.; Barroso, José G.; Pedro, Luis G.; Cristina Figueiredo, A.; Figueiredo, Ana Cristina; Rubiolo, Patrizia
ABSTRACT The chemical variability of the essential oils isolated from Moroccan chamomile [Cladanthus mixtus (L.) Chevall.] full flowering aerial parts, was evaluated. C. mixtus populations were collected from nine regions in Morocco: Benguerir, Bouznika, Chefchaouane, Kenitra, Meknes, Oujda, Settat, Sidi Alal Ibahraoui and Tamesna. The essential oils were isolated by hydrodistillation and analysed by gas chromatography and gas chromatography–mass spectrometry. The yields of the essential oils ranged between 0.1% and 0.8% (v/d.w.). Only five of the nine essential oil samples analysed showed good correlation after agglomerative cluster analysis based on the chemical composition of the essential oils. These samples (Benguerir, Kenitra, Settat, Meknes and Tamesna) were characterized by the dominance of camphor (14–27%), β‐myrcene (3–17%) and santolina triene (3–15%). All these and Chefchaouane essential oils showed a blue colour, whereas Oujda, Bouznika and Sidi Alal Ibahraoui essential oils were yellow. β‐Myrcene (3–17%), trans‐β‐farnesene (18%) and 2‐tridecanone (16%) dominated the Chefchaouane essential oil, whereas trans‐β‐farnesene (43%) was the main component in the Oujda essential oil. 2‐Methyl‐2‐trans‐butenyl methacrylate (34%) dominated sample Bouznika, while santolina alcohol and 1, 8‐cineole (17% and 12%, respectively) in the Sidi Alal Ibahraoui essential oil. The variability of Moroccan chamomile essential oil may reflect negatively upon its quality, biological activity and commercial value, thus harvests from the wild population should be avoided. To meet the high‐quality standards and production efficiency, cultivation techniques adapted to local soil types and weather conditions, as well the correct selection of plant varieties most suited to the market should be followed. Copyright © 2013 John Wiley & Sons, Ltd.